Preliminary in situ teeth study of the narrow‐ridged finless porpoises remains using microsynchrotron radiation X‐ray fluorescence and laser ablation inductively coupled plasma mass spectrometry. (21st June 2018) - Zheng, Yi; Zhang, Ya; Tang, Wenqiao; Guo, Hongyi; Zhu, Yan; Dong, Zhaohui; Jiang, Hui
Abstract : In recent years, a growing number of the narrow‐ridged finless porpoises were found dead near the Yangtze River estuary. In this region lived two sympatric subspecies, respectively, the East Asian finless porpoise and the Yangtze finless porpoise. So far, it is difficult to distinguish these two subspecies due to their similar shape and unavailable molecular marker. In this work, synchrotron radiation X‐ray fluorescence (SRXRF) and laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS) were applied for in situ teeth trace chemical analysis to study subspecies identification and migration near the Yangtze River estuary. Teeth Sr concentration and 87 Sr/ 86 Sr ratios, determined by SRXRF and LA‐ICP‐MS techniques, have potential application in the identification of the finless porpoise subspecies. Only one (Sample S4) of the six samples was concluded as the Yangtze finless porpoise, and the others were the East Asian finless porpoise. This study also proved that the Sr/Ca and Zn/Ca ratios could be used as a useful environmental indicator to detect the migratory history of narrow‐ridged finless porpoises.